Teaching Writing Using Google Apps For Education (GAFE) - Afrianto Daud (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This paper presents how an English teacher can use Google Apps for Education (GAFE) technology to enhance the quality of teaching writing in the context of teaching English for students in a higher education in Indonesia. This paper will briefly introduce some Google applications which can be used for (Engliah) teachers to enhance their teaching. It specifically reports a technology based teaching technique which has been practiced in a teacher education program in a university in Indonesia. It explores the prerequisite condition to use this application. This is followed by detailed stages of using this application, particularly in teaching writing: what teachers and students should do during the lesson. The explanation is enriched by a discussion on some possible challenges an English teacher or students may face in the field. The discussion is finally closed by proposing some suggestions on how to make use the technology and how to deal with the potential problems.